2014
DOI: 10.1080/23299460.2014.963004
|View full text |Cite
|
Sign up to set email alerts
|

Quality criteria and indicators for responsible research and innovation: learning from transdisciplinarity

Abstract: The concept of 'responsible innovation' (RI) or 'responsible research and innovation' (RRI) is rapidly gaining currency. However, a persistent critique is that without more concrete elaboration, the interpretive flexibility of the concept is so broad as to effectively render it meaningless. The articulation of quality criteria and indicators therefore seems crucial for RRI to be understood and operationalized by researchers, research funders, innovators and other relevant stakeholders. In this paper, we specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
153
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 29 publications
(26 reference statements)
1
153
0
2
Order By: Relevance
“…Responsible innovation is a rubric for guiding innovation toward socially and ethically acceptable ends (Stilgoe et al, 2013) with links to European technology assessments as well as to corporate social responsibility (Iatridis & Schroeder, 2016). Unlike corporate social responsibility, responsible innovation is meant to seek redress for ethical considerations often made invisible within an innovation's ecosystem, including existing inequities; this means that, unlike with corporate social responsibility methods for engaging "stakeholders", responsible innovation prioritizes the inclusion of rights holders historically marginalized in innovation decision processes (e.g., under-represented genders, see Wickson & Carew, 2014). As well, unlike technology assessments that consider pros and cons or risks and benefits, responsible innovation leads with broader and valuesbased inquiries into innovations in society.…”
Section: An Important Question Is Thus: How Do Smart Farming's Decismentioning
confidence: 99%
See 1 more Smart Citation
“…Responsible innovation is a rubric for guiding innovation toward socially and ethically acceptable ends (Stilgoe et al, 2013) with links to European technology assessments as well as to corporate social responsibility (Iatridis & Schroeder, 2016). Unlike corporate social responsibility, responsible innovation is meant to seek redress for ethical considerations often made invisible within an innovation's ecosystem, including existing inequities; this means that, unlike with corporate social responsibility methods for engaging "stakeholders", responsible innovation prioritizes the inclusion of rights holders historically marginalized in innovation decision processes (e.g., under-represented genders, see Wickson & Carew, 2014). As well, unlike technology assessments that consider pros and cons or risks and benefits, responsible innovation leads with broader and valuesbased inquiries into innovations in society.…”
Section: An Important Question Is Thus: How Do Smart Farming's Decismentioning
confidence: 99%
“…Wickson and Carew (2014) have shown that open design projects can enable interaction between wider social values and technological potential; at the design stage, innovations are not yet entrenched into infrastructures (e.g., regulations) or cultural habits, which means early intervention can help mitigate the dreaded "lag" between proscriptive policy making and rapid technological change (Ogburn, 1957).…”
Section: Kelly Bronsonmentioning
confidence: 99%
“…Moreover, being among the first accounts of RI to be published, the VS account has been widely cited (see Timmermans 2017) and discussed by the literature on RRI (e.g. Davis and Laas 2014;Wickson and Carew 2014;Zwart et al 2014), and used by dedicated RRI projects (see, e.g., GREATProject 2013; RRI Tools Project 2016). And, although they do not build on it, in the discussion of their own SOM account, the authors refer to the VS account as well.…”
Section: Von Schombergmentioning
confidence: 99%
“…However, rather than constituting a new account by themselves, several of the accounts were compiled out of pre-existing accounts and, therefore, were considered to lack novelty (second requirement). For this reason, for example, the accounts by Sutcliffe (2011), the RRI tools project (Klaassen et al 2014), and Wickson and Carew (2014) are left out. Lastly, the level of influence of an account (third requirement) was established by consulting an elaborate discourse analysis by Timmermans (2015b) that ranked publications and their authors based on cross-citation scores and their membership of RI projects.…”
Section: Step 1: Source Selectionmentioning
confidence: 99%
See 1 more Smart Citation